Short-term efficacy of dapagliflozin in children with hereditary proteinuric kidney disease - Cui, J Y (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2023)
Objective: To explore the short-term efficacy and safety of dapagliflozin in children with hereditary proteinuric kidney disease. Methods: This was a prospective cohort study. From August 2020 to December 2021, 23 children with hereditary kidney disease from Children's Hospital of Fudan University were enrolled. Patients received dapagliflozin 5 mg/d (weight≤30 kg) or initial dose 5 mg/d for 1 week, then 10 mg/d (weight>30 kg) and the dose of angiotensin converting enzyme inhibitors was stable during treatment. Clinical data including demographic parameters, primary diagnosis, estimated glomerular filtration rate (eGFR), 24 h proteinuria and characteristics in the follow-up were collected. The primary outcome was the change in 24 h proteinuria at 12 (±2) weeks, secondary outcomes included changes of 24 h proteinuria at 24 (±2) weeks, eGFR at both 12 (±2) and 24 (±2) weeks. The data were analysed by using mixed linear model. Results: Totally 23 patients were enrolled, including 16 males and 7 females. The age was (10.8±2.9) years. The primary diseases were Alport syndrome (12 cases), Dent disease (5 cases), proteinuria (4 cases), and focal segmental glomerulosclerosis (2 cases) respectively. Primary outcome showed that 24 h proteinuria decreased from baseline at 12 (±2) weeks during treatment (1.75 (1.46, 2.20) vs. 1.84 (1.14, 2.54) g/m2, P<0.05). Secondary outcomes showed that there was no significant difference in 24 h urine protein at 24 (±2) weeks (P>0.05). eGFR decreased slightly at 12 (±2) weeks ((107±21) vs. (112±28) ml/(min·1.73m2), P<0.05), and there was no significant difference at 24 (±2) weeks (P>0.05). Serum albumin increased at 12 (±2) and 24 (±2) weeks following the treatment ((39±8) vs. (37±8) g/L, (38±7) vs. (37±8) g/L, both P<0.05). No hypoglycemia event was reported during the treatment. Conclusion: The dapagliflozin had therapeutic effects on decreasing proteinuria and increasing serum albumin in short-term treatment in children with hereditary proteinuric kidney disease, no hypoglycemia or serious adverse events were observed